The Clinical Significance of Procalcitonin Elevation in Patients over 75 Years Old Admitted for COVID-19 Pneumonia - Andrea Ticinesi; Antonio Nouvenne; Beatrice Prati; Loredana Guida; Alberto Parise; Nicoletta Cerundolo; Chiara Bonaguri; Rosalia Aloe; Angela Guerra; Tiziana Meschi (Hindawi Limited, 2021)
Aim. To investigate the clinical significance of procalcitonin (PCT) elevation on hospital admission for coronavirus disease-19 (COVID-19) and its association with mortality in oldest old patients (age>75 years). Methods. The clinical records of 1074 patients with chest high-resolution computed-tomography (HRCT) positive for interstitial pneumonia and symptoms compatible for COVID-19, hospitalized in medical wards during the first pandemic wave in a single academic center in Northern Italy, were retrospectively analyzed. All patients had serum PCT testing performed within six hours from admission. Information on COVID-19-related symptoms, comorbidities, drugs, autonomy in daily activities, respiratory exchanges, other routine lab tests, and outcomes were collected. Clinical characteristics were compared across different admission PCT levels and ages. The association of admission PCT with mortality was tested separately in participants aged>75 and ≤75 years old by stepwise multivariate Cox regression model with forward selection. Results. With increasing classes of PCT levels (<0.05, 0.05-0.49, 0.5-1.99, and ≥2 ng/ml), there was a significant trend (P<0.0001) towards older age, male gender, wider extension of lung involvement on HRCT, worse respiratory exchanges, and several other laboratory abnormalities. Each incremental PCT class was associated with increased risk of hospital death at multivariate models in subjects older than 75 (hazard ratio for PCT≥2 vs. <0.05 ng/ml: 30.629, 95% confidence interval 4.176-224.645, P=0.001), but not in subjects aged 75 or younger. Conclusions. In patients admitted for COVID-19, PCT elevation was associated with several clinical, radiological, and laboratory characteristics of disease severity. However, PCT elevation was strongly associated with hospital mortality only in oldest old subjects (age>75).